Robotic-Assisted Laparoscopic Sacrocolpopexy for Pelvic Organ Prolapse: A Single Center Experience in China. (12th January 2022) - Niu, Ke; Zhai, Qingzhi; Fan, Wensheng; Li, Li'an; Yang, Wen; Ye, Mingxia; Meng, Yuanguang
Abstract : Objective . The aim is to investigate the efficiency and outcome of robotic-assisted sacrocolpopexy (RASC) in a cohort of patients with pelvic organ prolapse (POP) in our Gynecology Department. Methods . We performed a retrospective study of female patients who underwent RASC in Chinese PLA General Hospital from January 2013 to December 2020. Their clinical features included age, degree of prolapse, menopause time, body mass index, pregnancy, delivery, operation time, and bleeding volume. All patients were followed up for more than 6 months. POP-Q was recorded to evaluate the position of prolapsed organs. PFDI-20, PFIQ-7, and PGI-I were used to evaluate the life quality after surgery. Results . Twenty-four patients with POP received RASC in our center. The intraoperative bleeding was 86.9 ± 98.3 ml (20–300 ml). The operation time was 143.5 ± 47.3 min (60–240 minutes). The hospitalization time was 10.4 ± 2.1 days (8–16 days). And the follow-up time was 40.8 ± 22.0 months (6–72 months). In the POP-Q follow-up, postoperative Aa, Ba, Ap, Bp, and C were significantly improved than those before surgery (P < 0.05 ). The objective and subjective cure rate was 100%. PGI-I score was very good in 9 (9/24), very good in 10 (10/24), and good in 3 (3/24). Postoperative PFDI-20 and PFIQ-7 were 2.78 ± 3.82 and 1.57 ± 3.86, which decreased dramatically after surgery (P < 0.05 ). Mesh exposure occurred in 4 cases (16.7%) at 2–12 months. The exposed diameters were less than 1 cm in 3 cases (2 A/T3/S1) and 1-2 cm in 1 case (3 B/T3/S1). These mesh exposures healed after conservative observation or mesh excision. Conclusion . RASC for POP has the advantage of less bleeding and hospitalization time. It is a minimally invasive option for pelvic organ prolapse.